Global MHD Simulation of the Weak Southward IMF Condition for Different Time Resolutions - Park, Kyung Sun (Frontiers in Astronomy and Space Sciences, 2021)
We performed high-resolution three-dimensional global MHD simulations to determine the impact of weak southward interplanetary magnetic field (IMF) (Bz = -2nT) and slow solar wind to the Earth’s magnetosphere and ionosphere. We considered two cases of differing, uniform time resolution with the same grid spacing simulation to find any possible differences in the simulation results. The simulation results show that dayside magnetic reconnection and tail reconnection continuously occur even during the weak and steady southward IMF conditions. A plasmoid is generated on closed plasma sheet field lines. Vortices are formed in the inner side of the magnetopause due to the viscous-like interaction, which is strengthened by dayside magnetic reconnection. We estimated the dayside magnetic reconnection which occurred in relation to the electric field at the magnetopause and confirmed that the enhanced electric field is caused by the reconnection and the twisted structure of the electric field is due to the vortex. The simulation results of the magnetic field and the plasma properties show quasi-periodic variations with a period of 9 to 11 minutes between the appearances of vortices. Also the peak values of the cross-polar cap potential are both approximately 50 kV, the occurrence time of dayside reconnections are the same, and the polar cap potential patterns are the same in both cases. Thus, there are no significant differences in outcome between the two cases.